Biocompatibility, physico-chemical and mechanical properties of hydroxyapatite-based silicon dioxide nanocomposites for biomedical applications. Issue 15 (15th October 2020) - Taha, Mohammed A.; Youness, Rasha A.; Ibrahim, Medhat
Abstract: High-energy ball milling was employed to prepare carbonated hydroxyapatite/silicon dioxide (CHA/SiO2 ) nanocomposites. Then, these nanocomposite powders were sintered at 900 and 1300 °C. XRD technique, FTIR spectroscopy and SEM were employed to examine the structure, molecular structure and microstructure of the sintered nanocomposites samples, respectively. Moreover, their mechanical properties were also measured. Furthermore, in vitro bioactivity and cytotoxicity of these nanocomposites were evaluated. The results indicated that the successive increases in SiO2 contents led to remarkable enhancement for densification behavior, mechanical properties and in vitro bioactivity of nanocomposites sintered at 900 °C. However, further increase in the sintering temperature to 1300 °C caused dramatic decreases in density and mechanical properties of nanocomposites. On the contrary, better bioactivity behavior was achieved. Amazingly, the obtained results revealed that the sample having the highest content of SiO2 and sintered at 900 °C had no toxic effects on bone-like cells while, that sintered at 1300 °C exhibited mild cytotoxicity. Based on the variations in the abovementioned properties, these nanocomposites can be used in different biomedical applications.